Alienação parental: uma análise dos aspectos jurídicos, sociais e da pretensão de criminalizar o fenômeno - Lerme, Júlia Steffen (Universidade do Vale do Rio dos Sinos, 2018)
The parental alienation, a phenomenon established by Richard Gardner in 1985 and regulated in Brazil by the Law nº 12.318/2010, is one of several consequences of the end of the conjugal society, bringing serious violations of the rights of children and adolescents. The article 2 of Law 12.318/2010 defines the phenomenon as the acts practiced by the alienator, that disturb the psychological formation of children and adolescents with the intention that the infant repudiates the other parent or to cause any harm to the bond between them. The law also brings measures to be applied to prevent and punish the alienator. Although, society is currently discussing the need for more effective action to punish the practice of such acts. In this sense, the National Congress is passing a bill that specifically seeks to criminalize parental alienation. However, it is necessary to analyze whether the criminalization of the conduct will have the effect of reducing the number of cases of parental alienation.
Keywords: Família; Alienação parental; Prevenção; Criminalização; Parental alienation; Prevention; Criminalization